When the stenting in the approach to superior vena cava syndrome allows radical treatment of non-small cell lung cancer at the diagnosis - Hilário Soldin, Inês (2024)
Superior vena cava syndrome is an oncological emergency. It is life-threatening in 15% of the cases. When it is severe and the presentation form of malignancy, a multidisciplinary diagnostic and therapeutic approach is challenging and urgent. We present the case of a patient with no previous cancer that came to the emergency department due to superior vena cava syndrome. He had oedema of the face, cervical region and upper limbs, dyspnoea and altered mental status. Chest computed tomography showed a superior vena cava syndrome secondary to a mediastinal mass. Considering the severity of the obstruction, the absence of histological diagnosis and distant metastasis, an endovascular stent was placed urgently, with rapid clinical improvement. Subsequently, we obtained a diagnosis of stage IIIA lung adenocarcinoma. After partial response to chemoradiotherapy, the patient started consolidation therapy with durvalumab. Six months after the diagnosis, there is no relapse.